PERENCANAAN SPESIFIKASI TEKNIS RUAS JALAN PROVINSI UNGGAN (KABUPATEN SIJUNJUNG)-PAMUSIAN (KABUPATEN TANAH DATAR) - Bayu Budi Irawan; Yossyafra Yossyafra; Darwizal Daoed (Racic : Rab Construction Research, 2022)
The Unggan-Pamusian road is a road that connects Sijunjung and Tanah Datar Regencies. The West Sumatra Provincial Government intends to carry out the construction of the road segment. The purpose of this research is to plan the technical specifications for provincial roads, identify traffic conditions, forecast average daily traffic and plan the pavement thickness design. The method used is the Road Geometric Design Guidelines Number 13/P/BM/2021. The results of the technical planning specifications for provincial roads are adjusted to the standards. The traffic condition of the Unggan-Pamusian road segment is classified as low traffic with a description of the early stages of local roads and can be upgraded to collector roads. Forecasting results obtained average daily traffic of 3,166 vehicles (2021) and 7,482 vehicles (2046). Type of AC pavement with a thickness of AC-WC 40 mm, AC-BC4 60 mm, AC-BC or AC-Base 75 mm, CTB3 150 mm and class A aggregate foundation 150 mm.